FORMAÇÃO DE EDUCADORAS E EDUCADORES DO MST-ES: CONEXÕES, DESAFIOS E POSSIBILIDADES ANTE A DIMENSÃO EDUCACIONAL DA REFORMA AGRÁRIA POPULAR - Franca, Dalva Mendes de (2022)
The thesis defended in this research has as its object of study the “professional development of educators of the MST-ES: connections, challenges and possibilities in the face of the educational dimension of the Popular Agrarian Reform”. As a main objective, it aims to analyze what has caused the MST-ES to choose, in the professional development offered to its educators, the theme of Popular Agrarian Reform (PAR), highlighting possible articulations with the praxis of the MST´s Pedagogy. It takes as theoretical background knowledge: Freire, Marx and Engels, Caldart, Arendt and Stedile, among others, whom, in their approaches, support the concept of omnilateral formation, in the search for human emancipation in all dimensions, having dialectics as the epistemological path. Thus, it articulates foundations that are intertwined with the understanding of the proposed Popular Agrarian Reform as a strategy of resistance to the model of capitalist agriculture of agribusiness, aiming the gathering of strength, in order to build a new agriculture Project, which seeks to contemplate the needs of the Brazilian people (MST, 2014). This qualitative study has as its methodological strategy the systematization of experience, as a research methodology of Popular Education, mediated by militant research, which emerges from the involvement and commitment to social struggles, according to Bringel and Varela (2016). The scope of the research involved several loci within the scope of the MST-ES: historical militants, members of the national, state and regional directorate, of the Education Sector, members of other organizational Sectors of the Movement, educators and landless children “Sem Terrinha”. The instruments used for data collection and production, were the following: interview, questionnaires with open and closed questions, conversation circles and participant observation, research field notes, and MST´s documental sources. The results indicate that the professional development offered by MST to its educators, in its challenges and connections with the educational dimension of the PAR, brings contributions to the formation of critical consciousness and the search for strategies to strengthen the anti-capitalist struggle and the MST´s Pedagogy. The MST in ES reaffirms the need to deepen and broaden this debate in educator´s professional development efforts, as a possibility to qualify educational experiences and cooperate with the processes of collective construction of the PAR, enhancing its study and production of new knowledge at school, in the camps and settlements, and opening dialogue with other fronts of struggle and resistance, aiming the building of another Popular Agrarian Project.